IMPACT OF SMOKING ON HEMATOLOGICAL PARAMETERS IN HYPERTENSION SMOKERS - Salman, Mustafa Abdulkareem; Rashid, Hiba Hadi (International Journal of Psychosocial Rehabilitation, 2020)
Objective: Tobacco smoking considered as the main causes of death in the world which leading to both acute and may chronic impacts on hematological parameters. In addition, hypertension is one of the health problems of the world. It may lead to cause cardiovascular disease furthermore cause functional disturbances to hematological parameters. Subsequently, it may enhance an organ damage. The aim of our study was to estimate the extent of adverse impacts of tobacco smoking on biochemical characteristics in hypertension comparing with healthy smokers. Methods: Our study was conducted from October 2019 to January 2020 on a total of 110 smokers who have hypertension and 100 who are healthy smokers individuals at Baqubah Teaching Hospital. The smokers were regularly consuming 30-45 cigarettes per day for at least for 4years. The ethical guidelines constructed by the Scientific Committee of the Institute have been taken where the acceptance have also taken from volunteers. Blood samples have been collected via EDTA tubes 3ml of blood and tested by fully automatic hematological analyzer (DIAGON Ltd- D-Cell 60). Conclusion: Excessive smoking with hypertension existing causing abnormal and significantly increases of hematological parameters which is lead to early atherosclerosis, cardiovascular diseases, polycythemiavera and chronic obstructive pulmonary disease.